Assessing population maturity of three perennial grass species: Influence of phenology and tiller demography along latitudinal and altitudinal gradients. (8th June 2013) - Rossignol, N.; Andueza, D.; Carrère, P.; Cruz, P.; Duru, M.; Fiorelli, J.‐L.; Michaud, A.; Plantureux, S.; Pottier, E.; Baumont, R.
Abstract To assess the whole‐sward maturity, which is a primary concern for grassland managers, we studied three forage grass species with contrasting phenology over a range of climatic conditions among sites. We considered two main issues: (i) How is grass population maturity related to population phenology, and is this relation affected by environmental factors? and (ii) Is the sum of temperatures a good index to describe phenological development under contrasting climates? To explore the role of temperature accumulation in species population development, we described the phenological development of populations of three grass species along latitudinal and altitudinal gradients at eight locations across France. We used a numerical index of tiller development to quantify sward morphological structure and discriminate phenological peak from average maturity. We report that phenological development rates were similar among sites for each species, but required fewer growing degree days to start at higher latitudes and altitudes. However, we found that population maturity and phenological peak differed significantly due to among‐site variability in vegetative tiller percentage in whole‐population biomass. Our results underlined the importance of considering tiller distribution among phenological stages, especially tiller development synchrony, together with phenology to assess sward maturity in semi‐natural permanent grasslands.